Lentinula edodes (shiitake mushroom): An assessment of in vitro anti-atherosclerotic bio-functionality - Rahman, Mohammad Azizur; Abdullah, Noorlidah; Aminudin, Norhaniza (Elsevier, 2018)
Mushrooms have been highly regarded as possessing enormous nutritive and medicinal values. In the present study, we evaluated the anti-oxidative and anti-atherosclerotic potential of shiitake mushroom (Lentinula edodes) using its solvent–solvent partitioned fractions that consisted of methanol:dichloromethane (M:DCM), hexane (HEX), dichloromethane (DCM), ethyl acetate (EA) and aqueous residue (AQ). The hexane fraction (1 mg/mL) mostly scavenged (67.38%, IC50 0.55 mg/mL) the 2,2-diphenyl-1-picryl hydrazyl (DPPH) free radical, contained the highest reducing capacity (60.16 mg gallic acid equivalents/g fraction), and most potently inhibited lipid peroxidation (67.07%), low density lipo-protein oxidation and the activity of 3-hydroxy 3-methyl glutaryl co-enzyme A reductase (HMGR). GC–MS analyses of the hexane fraction identified α-tocopherol (vitamin E), oleic acid, linoleic acid, ergosterol and butyric acid as the bio-functional components present in L. edodes. Our findings suggest that L. edodes possesses anti-atherosclerotic bio-functionality that can be applied as functional food-based therapeutics against cardiovascular diseases.